ASUHAN KEPERAWATAN PADA TN. H DENGAN PNEMONIA DI RSUD BANGKINANG - nurasikin; Yenny Safitri; Ridha Hidayat; Muhammad Nizar Syarif Hamidi (Jurnal Spektrum Kesehatan Indonesia, 2025)
Pneumonia is a lower respiratory tract infection characterized by inflammation of the lung tissue due to bacterial, viral, fungal, or aspiration of foreign substances. This disease is one of the main causes of morbidity and mortality, especially in the elderly. This case study aims to provide a comprehensive overview of the implementation of nursing care for pneumonia patients treated in the isolation room of Bangkinang Regional Hospital in 2025. The approach used is the nursing process method which includes assessment, determination of nursing diagnosis, planning, implementation, and evaluation. The subject of the study was a 61-year-old male patient with the main complaint of coughing up phlegm accompanied by blood, shortness of breath, fever, and weakness. Based on the results of the assessment and supporting examinations, several nursing diagnoses were determined, including: ineffective airway clearance, hyperthermia, activity intolerance, ineffective breathing patterns, and risk of nutritional deficit. Nursing interventions were carried out in accordance with the Indonesian Nursing Intervention Standards (SIKI). Evaluation showed an improvement in the patient's condition after nursing actions were carried out for three days. This study emphasizes the importance of systematic and continuous nursing care to improve the health status of pneumonia patients.